The dwarves - Heitz, Markus, 1971- (Orbit, 2009)
Abandoned as a child, Tungdil the blacksmith labors contentedly in the land of Ionandar, the only dwarf in a kingdom of men. Although he does not want for friends, Tungdil is very much aware that he is alone - indeed, he has not so much as set eyes on another dwarf. But all that is about to change. Sent out into the world to deliver a message and reacquaint himself with his people, the young foundling finds himself thrust into a battle for which he has not been trained. Not only his own safety, but the life of every man, woman and child in Girdlegard depends upon his ability to embrace his heritage. Although he has many unanswered questions, Tungdil is certain of one thing: no matter where he was raised, he is a true dwarf. And no one has ever questioned the courage of the Dwarves.